Social Justice Philanthropy Based on Zakat at the Persatuan Islam Amil Zakat Institution and its Contribution to Covid-19 Pandemic Mitigation in West Java - Hurun'in, Siti Zayyini; I Nurol Aen; Ahmad Hasan Ridwan; Badri Khaeruman (GoResearch - Research & Publishing House, 2024)
The Covid-19 pandemic, which began in 2020, has had various impacts on the socio-economic order, evidenced by declining public income, increasing unemployment, and a decrease in export-import activities, all of which have significantly raised the poverty level in Indonesia. Zakat, as an instrument of Islamic philanthropy aligned with its objectives, should be a solution for public welfare. Through MUI Fatwa No. 23 of 2020, zakat has undergone reinterpretation to reduce its exclusivity, demanding equitable social distribution. This research was conducted in West Java at the Persatuan Islam Amil Zakat Institution (LAZ PERSIS) to analyze: (1) The normative and historical foundations of philanthropy in Islam; (2) Social justice philanthropy activities based on zakat; (3) The contribution of social justice philanthropy based on zakat; and (4) The implications of this contribution for the socio-economic status of the community. The theory used is al-Maqāshid Syari’ah as the grand theory. The middle theory employs social justice philanthropy theory, and the applied theory uses tathbiq theory. This is qualitative research using an empirical juridical approach with a descriptive analysis method. The primary data sources for this research are the management of LAZ Persis and the community recipients of Covid-19 aid in West Java. The research findings include: First, the normative and historical foundations of Islamic philanthropy have existed in the Qur’an and Hadith and have been applied since the time of the Prophet Muhammad (SAW) until today. Second, social justice philanthropy activities based on zakat include (a) Health Assistance, (b) Basic Necessities, (c) Counseling and Advocacy, (d) Capital Assistance. Third, during the three-year pandemic period in West Java, from the WHO declaration on March 11, 2020, until the pandemic status was lifted in Indonesia on June 21, 2023, LAZ PERSIS contributed aid to 435,292 beneficiaries. Fourth, the research implications include theoretical and practical implications. The theoretical implication offers a new concept of “Holistic Integrative Philanthropy,” a form of social justice philanthropy based on zakat that is inclusive, collaborative, and professional. Practically, during the pandemic, LAZ PERSIS helped 79% of respondents maintain their economic conditions and minimize the risk of contracting the Covid-19 virus.